The Influence of Gayatri Mantra & Emotional Freedom Technique (GEFT) towards Mood Disorders Nurse Students in Thesis Compilation - Ni Kadek Ayu Cintya Dewi; Ni Luh Putu Thrisna Dewi; Ni Made Nopita Wati; Diah Prihatiningsih; Putu Gede Subhaktiyasa (MBUnivPress, 2021)
Thesis preparation results in students experiencing difficulties that cause psychological conditions that are distressed, causing emotional disorders such as mood disorders. Mood disorders can be bad for students and cause students to postpone their thesis. Efforts are made to overcome mood disorders when compiling thesis is to apply GEFT. GEFT is a merger between Gayatri Mantra and Emotional Freedom Technique (EFT). GEFT is done by chanting the Gayatri Mantra and giving a light knock on the body's 12 energy pathways called the energy meridians. The purpose of this study is to know the influence of GEFT towards mood disorders nurse students in thesis compilation. This research is quantitative with a quasi experiment research design pre and post with control group design. The sampling technique is purposive sampling with a total sample of 32 respondents divided into 2 groups the treatment group and the control group. Data were collected using The Brunel Mood Scale (BRUMS) questionnaire. Data analysis uses the Wilxocon Signed Rank Test and the Mann Whitney Test. The results showed the value of p value in the treatment group = 0.003 which means that there was an influence of GEFT on mood disorders of nursing students in preparing their thesis, whereas in the control group there was no difference with the value of p value = 0.317. Changes in students mood disorders after being given GEFT due to a combination of spiritual spells with techniques that support the effectiveness of GEFT.